Non-Governmental Organizations and Health in Developing Countries - Green, A. author. aut Link
XVI, 229 p.
Keywords: Non-governmental organizations (NGOs) are increasingly recognised as playing a significant role in the health sector in developing countries. This book examines the background to the growth both in the sector and interest in it, the strengths and weaknesses of NGOs and the arguments for and against their use for different aspects of the health sector. It focuses particularly on the relationship between the State and non-governmental organizations and the issues critical to the development of policies towards the sector.